Research on the availability grading of business systems in the data center - Ming LEI; Qin LIU; Duo FENG; Ling LIU (Dianxin kexue)
By analyzing the grading status of data centers at home and abroad and the availability of business systems in the data center,business availability grading recommendations,and business system requirements and configuration recommendations for the data center infrastructure were proposed,thus making the data center infrastructure more rational and reducing the cost of data center.